Minimally invasive robotic ureteral reconstruction using endoscopic submucosal dissection harvested colorectal mucosa graft for ureteral stricture - Haihang Nie; Yali Yu; Xiubing Chen; Jingkai Zhou; Xianglin Li; Yuntian Hong; Fan Wang; Chaoqi Liang; Bing Li; Haizhou Wang; Hongling Wang; Qiu Zhao; et al. (Scientific Reports)
Abstract To evaluate the feasibility and safety of using colorectal mucosal grafts (CMG) harvested via endoscopic submucosal dissection (ESD) for ureteral reconstruction in patients with ureteral stricture. Eight patients with ureteral stricture underwent robotic ureteral reconstruction using CMG harvested by ESD. Preoperative assessments included clinical history, physical examination, and various imaging studies. The ESD procedure was performed with standard precautions to obtain sufficient graft material. Postoperative follow-up involved endoscopic examinations and retrograde pyelograms to assess colorectal complication and ureteral patency. The average age of patients was 44 years, and the median BMI was 24.6 kg/m². The causes of stricture included ureteral stones, urinary tract infections, and ureteral polyps. The median stricture length was 3.5 cm. The average size of the harvested CMG was 4 × 2.4 cm. The success rate of the grafting procedure was 100%, with no gastrointestinal complications observed. Endoscopic examination one week postoperatively revealed well-healed wounds. No recurrent ureteral strictures were noted during a median follow-up period of 5 months. The average glomerular filtration rate (GFR) of the affected kidneys was 61 ml/min. Harvesting CMG via ESD for ureteral reconstruction is feasible and safe, with minimal complications and promising short-term outcomes. This technique provides a viable alternative for patients contraindicated for oral mucosal grafts, potentially reducing morbidity associated with traditional intestinal mucosa harvesting methods.